Unusual uterine metastasis of plasmablastic lenfoma: a case report - Karataş, Suat; Çift, Tayfur; Şal, Veysel; Tekelioğlu, Meltem; Ton, Özlem (The European Research Journal, 2019)
Plasmablastic lenfoma (PBL) is a diffuse large B-cell lymphoma (DLBCL)’s variant form that is especially reported in HIV-infected patients. PBL is a rare entity seen most commonly in the setting of immunocompromise. However, this disease may present in extraoral sites in which the genital tract appears to be the less common. Here we present a patient with uterine and fallopian mass diagnosed PBL. A 51-year-old multipara (G6P4C2) woman with a chief complaint of irregular vaginal bleeding was presented to our outpatient clinic. She had a prior history of breast cancer treated by right mastectomy and adjuvant chemotherapy.Transvaginal ultrasonography and magnetic resonance imaging both showed an uterine mass thought to be leiomyoma, which 4×3 cm in size on the anterior wall of uterin corpus. The pathology result of the mass was found to be plasmablastic lymphoma. Genital involvement also appears to be last but possible site option to find PBL focus in immunocompetent patients.